2016
DOI: 10.1128/microbiolspec.mchd-0011-2015
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts—Key Players in Skeletal Health and Disease

Abstract: Summary The differentiation of osteoclasts (OC) from early myeloid progenitors is a tightly regulated process that is modulated by a variety of mediators present in the bone microenvironment. Once generated, the function of mature OC depends on cytoskeletal features controlled by an αvβ3-containing complex at the bone-apposed membrane, and the secretion of protons and acid-protease cathepsin K. OC also have important interactions with other cells in the bone microenvironment including osteoblasts and immune ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 254 publications
(276 reference statements)
2
50
0
Order By: Relevance
“…The first is that by using a precisely measured trait, BMD, which is highly heritable with estimates from 50% to 85% and for which genetic determinants have been identified through GWAS, there do not appear to be associations between methylation changes and BMD. Although whole blood methylation changes may not be the ideal tissue within which to test epigenetic influences on bone, this conveniently accessible tissue has many links to bone biology, including the fact that osteoclasts and monocyte/macrophages originate from the same precursors . The extent to which methylation changes are shared between bone and whole blood is not well known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is that by using a precisely measured trait, BMD, which is highly heritable with estimates from 50% to 85% and for which genetic determinants have been identified through GWAS, there do not appear to be associations between methylation changes and BMD. Although whole blood methylation changes may not be the ideal tissue within which to test epigenetic influences on bone, this conveniently accessible tissue has many links to bone biology, including the fact that osteoclasts and monocyte/macrophages originate from the same precursors . The extent to which methylation changes are shared between bone and whole blood is not well known.…”
Section: Discussionmentioning
confidence: 99%
“…We studied epigenetic variation in whole blood, as a proxy for difficult‐to‐acquire samples such as bone, in relation to BMD because epigenetic markers are often stable across multiple tissues, and immune cells within blood are known to influence bone homeostasis . Furthermore, osteoclasts are derived from the monocyte‐macrophage lineage found in whole blood . Although epigenetic profiling has been performed previously in bone samples from osteoporotic and osteoarthritic patients and an epigenome‐wide association study (EWAS) of BMD has been performed in mice, EWAS of BMD have not been reported in humans with validation of significant findings.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, metabolic inflammation is a significant cause of osteoarticular symptoms in MPS disorders [183,198]. On the other hand, CTSs have long been involved in skeletal and bone health and disease [199]. Recently, up-regulation of CTSA, CTSH, and CTSZ has been detected through transcriptomic and proteomic analyses in a rat model of spinal cord injury [200].…”
Section: Cathepsin Involvement In the Pathophysiology Of Mucopolysaccmentioning
confidence: 99%
“…It is likely that UPR affects multiple cytokines in osteoblasts and osteocytes in addition to those described in this report. Besides VEGF and TNF, the UPR could have affected other locally produced cytokines that have been shown to influence RANKL expression such as IL‐1, IL‐6, IL‐11, oncostatin M and leukemia inhibitory factor . Additional studies will be required to ascertain the cytokines profile in response to elevated UPR in bone cells and better understand mechanism(s) – distinct or common – underlying their regulation and the interdependence of the affected cytokines in promoting bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of RANKL are also associated with and in some cases causally linked with other bone diseases like arthritis, orthopedic implant‐associated osteolysis, periodontitis, age‐dependent osteoporosis, as well as postmenopausal osteoporosis, and unloading‐induced bone loss . Some of these conditions are associated with increased inflammatory cytokines such as interleukin (IL)‐1 and tumor necrosis factor‐α (TNF‐α), that can directly stimulate RANKL synthesis and thereby augment bone resportion . In general, however, the signaling pathways and molecular mechanisms that contribute to elevated cytokine production in pathologic bone loss are not well defined.…”
Section: Introductionmentioning
confidence: 99%